Walking the tightrope: communicating overdiagnosis in modern healthcare. (5th February 2016) - McCaffery, Kirsten J; Jansen, Jesse; Scherer, Laura D; Thornton, Hazel; Hersch, Jolyn; Carter, Stacy M; Barratt, Alexandra; Sheridan, Stacey; Moynihan, Ray; Waller, Jo; Brodersen, John; Pickles, Kristen; et al.
Abstract : Communication that empowers the public, patients, clinicians, and policy makers to think differently about overdiagnosis will help support a more sustainable healthcare future for all, argue Kirsten McCaffery and colleagues